Mechanisms of substrate recognition and N6-methyladenosine demethylation revealed by crystal structures of ALKBH5–RNA complexes. Issue 7 (25th March 2022) - Kaur, Simranjeet; Tam, Nok Yin; McDonough, Michael A; Schofield, Christopher J; Aik, Wei Shen
Abstract: AlkB homologue 5 (ALKBH5) is a ferrous iron and 2-oxoglutarate dependent oxygenase that demethylates RNA N 6 -methyladenosine (m 6 A), a post-transcriptional RNA modification with an emerging set of regulatory roles. Along with the fat mass and obesity-associated protein (FTO), ALKBH5 is one of only two identified human m 6 A RNA oxidizing enzymes and is a potential target for cancer treatment. Unlike FTO, ALKBH5 efficiently catalyzes fragmentation of its proposed nascent hemiaminal intermediate to give formaldehyde and a demethylated nucleoside. A detailed analysis of the molecular mechanisms used by ALKBH5 for substrate recognition and m 6 A demethylation is lacking. We report three crystal structures of ALKBH5 in complex with an m 6 A-ssRNA 8-mer substrate and supporting biochemical analyses. Strikingly, the single-stranded RNA substrate binds to the active site of ALKBH5 in a 5′-3′ orientation that is opposite to single-stranded or double-stranded DNA substrates observed for other AlkB subfamily members, including single-stranded DNA bound to FTO. The combined structural and biochemical results provide insight into the preference of ALKBH5 for substrates containing a (A/G)m 6 AC consensus sequence motif. The results support a mechanism involving formation of an m 6 A hemiaminal intermediate, followed by efficient ALKBH5 catalyzed demethylation, enabled by a proton shuttle network involving Lys132 and Tyr139. Graphical Abstract: